Examination of the price discount on the external debt of developing countries. - ALFORD, Alan (1993)
Presents the results of a study which indicated that the market price of a debt is related to the existence of a moratorium on a country's debt repayment, to the level of interest rates, to the ratio of debt to GDP, to the ratio of arrears to external debt, and to the level of capital flight. The analysis, using two sub-groups of countries (South American and non-South American), emphasized those variables that denote a change in the confidence in future solvency, such as reschedulings and capital formation.